Development of Macromedia Flash Based Teaching Materials on It-Based Statistic Data Analysis - Wahyuni, Putri; Yolanda, Fitriana (Universitas PGRI Madiun, 2020)
This study aims to produce Macromedia flash-based teaching materials in IT-based statistical data analysis courses that are tested validity. The form of research carried out is research development under the term Research and Development (R&D). This research was conducted at the Faculty of Mathematics and Natural Sciences UIR Academic Year 2018/2019 in sixth-semester students. The research subjects in this study were sixth-semester students of UIP Mathematics FKIP. Based on the 4-D development model, the researcher made the design of this development procedure consisting of only 3 stages, namely defining, planning, and developing. The deployment stage (disseminated) was not carried out due to time and cost limitations. The data collection instrument in this study was a validation sheet of learning tools. The data analysis technique is an analysis technique used is the descriptive analysis that describes the validity of Macromedia flash-based teaching materials on IT-based statistical data analysis courses. From the research results obtained validity of Macromedia flash-based teaching materials meets the category of very valid with an average total of 87,955. Based on the research results it can be concluded that research has produced Macromedia flash-based teaching materials in valid IT-based statistical data analysis courses.